Contribuições da Teologia para os estudos do letramento: sensibilização para a empatia em práticas de letramento em escola pública - Campos, Paula Figueiredo (2017)
This research presents the literacy social practice of Think Aloud in Group – PAG (ZANOTTO, 1992, 1995), which I‘ve proposed to a group of students at the public school I work at in a city in the south of Minas Gerais. This is an action research, born from the need to investigate my own teaching practice in order to transform it. I advocate that dialog at literacy practices is essential to students‘ holistic school formation. Moreover, this is a main factor to recognizing every human being‘s personal dignity and alterity at public school literacy practices. I propose an interlocution between Theology and Literacy Studies to produce knowledge about how can the Brazilian public school teacher deal with the concrete reality of each human being he/she works with. Think Aloud in Group (PAG) is a literacy practice and research method in which the teacher must find a way to open space for the readers to feel comfortable to think collectively and collaboratively in order to solve controversial questions over text meanings and other subjects which may arise in the discursive interaction. Through PAG, it is possible to investigate how the researcher makes dialog possible at the literacy events. Dialog is a useful mean to sensitize students to experience empathy and to recognizing the alterity of every person present at the social interaction. Being empathic towards others is seen as a merciful action – theological concept of Francisco (2016a) - by which one can restitute human dignity of people considered unimportant by an individualistic and consumerist culture, where common good appears to have been forgotten. This research fits in at the qualitative and interpretative research tradition of the educational practice (ERICKSON, 1986), which minds to listen to the participators‘ voices (MOITA LOPES, 2006). It sees the researcher as an integral member of the social practice under study